Contextualizing urban living as a determinant of women's health in Jakarta, Indonesia. Issue 10 (26th November 2017) - Christiani, Yodi; Tavener, Meredith; Byles, Julie E.
ABSTRACT: Big cities can offer great opportunities for women to have a better life. At the same time, however, the physical and social environment in cities can negatively affect their health. We conducted focus groups with 24 women (aged 18–72 years) living in Jakarta, Indonesia from October to November 2014. Our aim was to elicit women's experiences of living in Jakarta, including their health and accessing health care. The most frequent health problems reported by women in this study were hypertension and arthritis. Women often gave priority to their family, particularly their children, over themselves and their own health. Discussants also thought that the city's physical and social conditions could affect their health, and that women were more prone to feel stress than men. The results of this study highlight the importance of addressing social determinants of health across the life course, including gender, to improve women's health status. Moreover, multi-sectoral collaboration at the municipal and national level is needed for urban planning to create better living conditions for women in the cities.